2008
DOI: 10.1002/jmri.21591
|View full text |Cite
|
Sign up to set email alerts
|

MR angiography of the cerebral perforating arteries with magnetization prepared anatomical reference at 7T: Comparison with time‐of‐flight

Abstract: Purpose: To develop a magnetic resonance imaging (MRI) protocol that visualizes both the perforating arteries and the related anatomy in a single acquisition at 7T. Material and Methods:T 1 -weighted magnetization prepared imaging (MPRAGE) was empirically modified for use as angiography method at 7T. The resulting sequence depicts the vasculature simultaneously with the surrounding anatomical structures, and is referred to as "magnetization prepared anatomical reference MRA" (MPARE-MRA). The method was compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
43
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 9 publications
1
43
0
1
Order By: Relevance
“…These findings were also consistent with the results of previous studies, which showed that 7.0-T TOF MRA provided only small increases in the signal-to-noise ratio in the primary intracranial vessels but provided better visualization of the first-and second-order branch arteries. 11,12,22,36,37 Meanwhile, in our study, MMVs in the sylvian fissure, interpeduncular cistern, and quadrigeminal cistern ( Fig. 2A and B) were visualized better on axial T2-weighted 7.0-T MR images.…”
Section: Discussionsupporting
confidence: 51%
“…These findings were also consistent with the results of previous studies, which showed that 7.0-T TOF MRA provided only small increases in the signal-to-noise ratio in the primary intracranial vessels but provided better visualization of the first-and second-order branch arteries. 11,12,22,36,37 Meanwhile, in our study, MMVs in the sylvian fissure, interpeduncular cistern, and quadrigeminal cistern ( Fig. 2A and B) were visualized better on axial T2-weighted 7.0-T MR images.…”
Section: Discussionsupporting
confidence: 51%
“…Hence, due to the local transmit coil setup at 7 T, a non-selective inversion recovery pulse is effectively a slab-selective inversion recovery pulse [36,37]. In a recent publication, Zwawanenburg et al [38] demonstrated the high diagnostic potential of nonenhanced MPRAGE MRI at 7 T for excellent assessment of cerebral perforating arteries and related anatomical parenchymatous structures. In two other recent studies on UIAs and intracranial arteriovenous malformations, the diagnostic potential of MPRAGE has been shown [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…2). Besides structural imaging, first studies on 7 Tesla brain MRI disclosed an interesting characteristic of T1-weighted imaging at 7 T, by means of a homogeneously hyperintense delineation of arterial vasculature [31,32]. The etiology of this feature is incompletely understood so far.…”
mentioning
confidence: 99%